The development of a lexicon for cashew nuts. Issue 1 (31st January 2017) - Griffin, L. E.; Dean, L. L.; Drake, M. A.
Abstract: A lexicon of flavor and texture terms was developed to describe the sensory characteristics of cashew nuts. A highly trained and experienced descriptive analysis panel ( n  = 10, ages 22–58 each with at least 60 hr of descriptive work in nuts) was used to create the lexicon for cashews. After initial identification and discussion of terms, 22 flavor terms, 4 texture terms, and 3 feeling factors to describe the sensory attributes of cashews were identified. The lexicon was validated by demonstrating that the panel could detect differences among 18 different cashew samples, including raw, oil‐roasted, dry‐roasted, skin‐on, store‐brand, national‐brand, and rancid types when using the identified lexicon. The differences in products were analyzed using analysis of variance and principal component analysis. Differences in flavor and texture were observed across all product categories and the lexicon was validated. Practical applications: The lexicon is intended for use in cashew research and by the cashew industry as a way for communicating differences in cashew flavor and texture in a common language.